2014
DOI: 10.1002/2014gl059819
|View full text |Cite
|
Sign up to set email alerts
|

High‐precision relocation of long‐period events beneath the summit region of Kı̄lauea Volcano, Hawai‘i, from 1986 to 2009

Abstract: Long‐period (0.5–5 Hz, LP) seismicity has been recorded for decades in the summit region of Kı̄lauea Volcano, Hawai‘i, and is postulated as linked with the magma transport and shallow hydrothermal systems. To better characterize its spatiotemporal occurrence, we perform a systematic analysis of 49,030 seismic events occurring in the Kı̄lauea summit region from January 1986 to March 2009 recorded by the ∼50‐station Hawaiian Volcano Observatory permanent network. We estimate 215,437 P wave spectra, considering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
(68 reference statements)
4
40
0
Order By: Relevance
“…Shallow LP locations are relatively well constrained (2-3 km horizontal and~3 km vertical resolution) and agree with previous studies [Matoza et al, 2014], while tremor locations have large errors (5-8 km), particularly in depth (15+ km), where locations concentrate at the bottom of our grid. This large uncertainty is the result of coarse timing obtained from smoothed (0.2 Hz) envelopes, a problem exacerbated by the seismic network geometry.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…Shallow LP locations are relatively well constrained (2-3 km horizontal and~3 km vertical resolution) and agree with previous studies [Matoza et al, 2014], while tremor locations have large errors (5-8 km), particularly in depth (15+ km), where locations concentrate at the bottom of our grid. This large uncertainty is the result of coarse timing obtained from smoothed (0.2 Hz) envelopes, a problem exacerbated by the seismic network geometry.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…For example, the Boso Peninsula is covered by the same dense network of seismometers as other locations in Japan where tectonic tremor has been observed, and the SSEs are shallower than in southwest Japan. At Kīlauea, seismic instrumentation is dense in order to monitor volcanic activity, and volcanic tremor has been regularly detected by the seismic network and recorded for decades at Kīlauea's summit and in its radial rift zones [Aki et al, 1977;Goldstein and Chouet, 1994;Montgomery-Brown et al, 2013;Matoza et al, 2014]. In New Zealand, however, tremor was not detected during SSEs with a sparse seismic network [Delahaye et al, 2009], but was discovered after instrumental densities were increased [Kim et al, 2011;Fry et al, 2011].…”
Section: Instrument Density and Tremor Amplitudesmentioning
confidence: 99%
“…These events may be related with the 1997 East Rift Zone (ERZ) eruption, which lacked precursory summit inflation, probably because of its occurrence in response to a decrease of the rift zone-perpendicular normal stress due to flank motion [Owen et al, 2000;Segall et al, 2001;Almendros et al, 2001;Desmarais and Segall, 2007]. The eruption started in the morning of 30 January 1997 and lasted 22 h. We compared these earthquakes with the LP events in Matoza et al [2014] and found out that 451 of them are identified as LP events. Matoza et al [2014] stated that the LP event catalog especially the shallow events can be slightly incomplete.…”
Section: Event Type and Timementioning
confidence: 99%